Muscle glycogen content during endurance training under low energy availability - Kojima, C.; Ishibashi, A.; Tanabe, Y.; Iwayama, K.; Kamei, A.; Takahashi, H.; Goto, K. (Medicine & Science in Sports & Exercise, 2020)
PURPOSE: The present study investigated the effects of three consecutive days of endurance training under conditions of low energy availability (LEA) on the muscle glycogen content, muscle damage markers, endocrine regulation, and endurance capacity in male runners. METHODS: Seven male long-distance runners (19.9 ± 1.1 yr, 175.6 ± 4.7 cm, 61.4 ± 5.3 kg, maximal oxygen uptake [V?O2max]: 67.5 ± 4.3 mL·kg·min) completed two trials consisting of three consecutive days of endurance training under LEA (18.9 ± 1.9 kcal·kg FFM·d) or normal energy availability (NEA) (52.9 ± 5.0 kcal·kg FFM·d). The order of the two trials was randomized, with a 2-wk interval between trials. The endurance training consisted of 75 min of treadmill running at 70% of V?O2max. Muscle glycogen content, respiratory gas variables, and blood and urine variables were measured in the morning for three consecutive days of training (days 1-3) and on the following morning after training (day 4). As an indication of endurance capacity, time to exhaustion at 19.0 ± 0.8 km·h to elicit 90% of V?O2max was evaluated on day 4. RESULTS: During the training period, body weight, fat-free mass, and skeletal muscle volume were significantly reduced in LEA (P = 0.02 for body weight and skeletal muscle volume, P = 0.01 for fat-free mass). Additionally, muscle glycogen content was significantly reduced in LEA (~30%, P < 0.001), with significantly lower values than those in NEA (P < 0.001). Time to exhaustion was not significantly different between the two trials (~20 min, P = 0.39). CONCLUSIONS: Three consecutive days of endurance training under LEA decreased muscle glycogen content with lowered body weight. However, endurance capacity was not significantly impaired.